Plerixafor on‐demand combined with chemotherapy and granulocyte colony‐stimulating factor: significant improvement in peripheral blood stem cells mobilization and harvest with no increase in costs. (21st October 2013) - Milone, Giuseppe; Martino, Massimo; Spadaro, Andrea; Leotta, Salvatore; Di Marco, Annalia; Scalzulli, Potito; Cupri, Alessandra; Di Martina, Valentina; Schinocca, Elena; Spina, Eleonora; Tripepi, Giovanni
Summary To date, no prospective study on Plerixafor 'on‐demand' in combination with chemotherapy and granulocyte colony‐stimulating factor (G‐CSF) has been reported. We present an interim analysis of the first prospective study in which Plerixafor was administered on‐demand in patients affected by multiple myeloma and lymphoma who received high dose cyclophosphamide or DHAP (dexamethasone, cytarabine, cisplatin) plus G‐CSF to mobilize peripheral blood stem cells (PBSC). One hundred and two patients were evaluable for response. A cohort of 240 patients receiving the same mobilizing chemotherapy was retrospectively studied. Failure to mobilize CD34+ cells in peripheral blood was reduced by 'on‐demand' strategy compared to conventional mobilization; from 13·0 to 3·0% (P = 0·004). Failure to harvest CD34+ cells 2 × 106/kg decreased from 20·9 to 4·0% (P = 0·0001). The on‐demand Plerixafor strategy also resulted in a lower rate of mobilization failure (P = 0·03) and harvest failure (P = 0·0008) when compared to a 'bias‐adjusted set of controls'. Evaluation of economic costs of the two strategies showed that the overall cost of the two treatments were comparable when salvage mobilizations were taken into account. When in combination with cyclophosphamide or DHAP plus G‐CSF, the 'on‐demand' use of Plerixafor showed, in comparison to conventionally treated patients, a significant improvement in mobilization of PBSC with no increase in overall cost.